2019
DOI: 10.1021/jacs.8b11445
|View full text |Cite
|
Sign up to set email alerts
|

Solution NMR Analysis of Ligand Environment in Quaternary Ammonium-Terminated Self-Assembled Monolayers on Gold Nanoparticles: The Effect of Surface Curvature and Ligand Structure

Abstract: We report a solution NMR-based analysis of (16-mercaptohexadecyl)­trimethylammonium bromide (MTAB) self-assembled monolayers on colloidal gold nanospheres (AuNSs) with diameters from 1.2 to 25 nm and gold nanorods (AuNRs) with aspect ratios from 1.4 to 3.9. The chemical shift analysis of the proton signals from the solvent-exposed headgroups of bound ligands suggests that the headgroups are saturated on the ligand shell as the sizes of the nanoparticles increase beyond ∼10 nm. Quantitative NMR shows that the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(128 citation statements)
references
References 55 publications
10
116
1
1
Order By: Relevance
“…It should also be noted that for the T 2 NMR experiments only the terminal protons are shown, H25 in Fig. 7b, because the protons farthest from the nanoparticle surface have been shown 60,62 to have the longest T 2 due to increase mobility in solution. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It should also be noted that for the T 2 NMR experiments only the terminal protons are shown, H25 in Fig. 7b, because the protons farthest from the nanoparticle surface have been shown 60,62 to have the longest T 2 due to increase mobility in solution. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meng et al . investigated the potential difference between MTAB ligands at the ends and the sides of gold nanorods (AuNRs) using chemical shift perturbation and T 2 relaxation . As compared to the spherical AuNPs, MTAB‐AuNRs have two distinctly different chemical environments (elongated sides and spherical ends) due to the rod‐like nature of the nanoparticle.…”
Section: Results From Different Nanoparticle Systemsmentioning
confidence: 99%
“…As compared to the spherical AuNPs, MTAB‐AuNRs have two distinctly different chemical environments (elongated sides and spherical ends) due to the rod‐like nature of the nanoparticle. Both T2 and T2* relaxation times were compared for different aspect ratios of MTAB‐AuNRs . When the aspect ratio increased, the difference between T2 and T2* also increased, and from this data, the authors concluded that the MTAB headgroup mobility depends on the nanorod aspect ratio.…”
Section: Results From Different Nanoparticle Systemsmentioning
confidence: 99%
“…Um weitere Erkenntnisse über die Verteilung der im Oberflächenstabilisator vorhandenen Elemente zu gewinnen, wurde die energiedispersive Röntgenspektroskopie (EDX) implementiert, während die Röntgen‐Photoelektronenspektroskopie (XPS) verwendet wurde, um das Vorhandensein bestimmter Elemente sowie deren chemische Berschaffenheit zu untersuchen. Auch die Kernspinresonanz (NMR)‐Spektroskopie wurde verwendet, um den Bindungsmodus eines Oberflächenstabilisators auf der Metalloberfläche zu untersuchen. Die thermogravimetrische Analyse (TGA) kann anhand der Thermostabilität das Vorhandensein eines Oberflächenstabilisators nachweisen.…”
Section: Charakterisierungsmethodenunclassified